The genus Rhodocollybia (Omphalotaceae, Basidiomycota) in the Republic of Korea - Ryoo, Rhim; Ka, Kang-Hyeon; Antonín, Vladimír (Phytotaxa, 2024)
Collections of Rhodocollybia from the Republic of Korea have been studied. Four species are recognized in the area. Three new species, Rhodocollybia butyraceoides, R. hongneungensis and R. variabilicolor, are described based on their macro- and micromorphological and phylogenetic characteristics. A detailed macro- and micromorphological description of R. maculata based on the Korean collection is also given. Taxonomic and phylogenetic positions of all taxa have been inferred and confirmed by analyses of ITS and LSU sequence data. A key to the Korean taxa is provided.